DAMPAK INDUSTRIALISASI TERHADAP POLA KEHIDUPAN SOSIAL DAN BUDAYA MASYARAKAT DI KOTA CILEGON KECAMATAN CIWANDAN - Insania, Insania khoiriyah; Khoirul Anam; Farha rizqi imara; Nauratu Syifa; Nazswa Prenita Anggraini; Azzahra Mutiara Fany; Nabila Viana Putri; Nafalie Cheisya Dermawan; Lilis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Industrialization is one of the factors influencing economic development and the lives of people in a region. Ciwandan District in Cilegon City is a rapidly growing industrial area, with numerous industrial companies established in the area. This industrial development has brought about various changes in the social and cultural life of the surrounding community. This study aims to determine the impact of industrialization on the social and cultural patterns of the community in Ciwandan District, Cilegon City. The study used a library research method, collecting data from various journals, scientific articles, books, and previous research related to industrialization in Cilegon City. The results indicate that industrial development has positive impacts in the form of job opportunities, increased community income, and the development of small businesses around the industrial area. However, industrialization also has negative impacts such as increased urbanization, changes in social interaction patterns, a decline in local cultural values, and environmental pollution due to industrial activities. Furthermore, the influx of immigrants from various regions also impacts the lifestyle of the community in Ciwandan District. Therefore, industrial development must be balanced with attention to social, cultural, and environmental conditions to maintain community well-being.